Pengaruh Motivasi, Disiplin, Stres Kerja Dan Gaya Kepemimpinan Terhadap Prestasi Kerja Karyawan Pada PT. Tiki Jalur Nugraha Ekakurir Aek Kanopan - Marto Hendry, Raja Saul (Universitas Labuhanbatu, 2021)
The purpose of this study was to determine the effect of analysis of motivation, discipline, work stress and leadership style on employee performance at PT Tiki Jalur Nugraha Ekakurir AEK Kanopan Kotapinang District Labuhanbatu Selatan Regency either partially or simultaneously. The sample in this study amounted to 34 people. The analysis method used is descriptive analysis, classical assumption test, multiple Linear regression analysis, T test, F test, and coefficient of determination and the data is processed using the IBM SPSS Statistics 23 program. The results of the hypothesis test showed that partially motivation has a positive and significant effect on employee performance, it is seen from the value of thitung for location is thitung 2.712 > ttable 1.697, with a significant value of 0.005 < 0.05. Discipline has a positive and significant effect on employee performance, it is seen from the value of Thitung for Discipline is thitung 2.694 > ttable 1.697, with a significant value of 0.009 < 0.05. Work stress has a positive and significant effect on Employee Performance, This can be seen from the value of thitung for work stress is thitung 2.677 > ttable 1.697, with a significant value of 0.015 < 0.05. Leadership style has a positive and significant effect on Employee Performance This can be seen from the value of thitung for leadership style is thitung 2.431 > ttable 1.697, with a significant value of 0.025< 0.05. Ftable value is 2.70, then based on the calculation results show that the value of F count 14.241 >2.70, and the significant value of 0.046 < 0.05. This shows that simultaneously The Independent Variable has a positive and significant effect on the Dependent variable.